Denials as Defense Mechanism of Jay Gatsby in The Great Gatsby (2013) Movie - Dewi, Cinthya Nisrina; Bustam, Muhammad Rayhan (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2024)
This research aims to analyse denial as defense mechanism in main character of The Great Gatsby (2013) movie, Jay Gatsby. This research discovered denials as defense mechanism in psychoanalytic in the main character, which based on Sigmund Freud's theory. The researcher used a qualitative descriptive method based on the movie’s dialogue and character’s behaviour. The Great Gatsby (2013) movie was the primary data source in this research. This research identifies 3 types of denial as defense mechanism in Jay Gatsby's character. Jay Gatsby shows that his denials were caused of his own ego, that he can’t accept reality he was born in a poor family and his unhealthy obsession towards Daisy Buchanan which their relationship has ended long time ago and now Daisy is already Tom Buchanan’s wife. Keywords: Pyschoanalysis, Defense Mechanism, Denial